THE ROLE OF DIGITAL FINANCIAL LITERACY IN SHAPING BEHAVIORAL INTENTION TO USE DIGITAL PAYMENTS AMONG MSMES - Husnul Hotimah hotim; Nurul Huda (Jurnal Ekonomi Syariah Indonesia (JESI), 2026)
Digital transformation in the financial sector has driven the use of digital payments as one of the important instruments in enhancing efficiency and financial inclusion for MSMEs. However, the level of digital payment adoption among MSMEs still faces various challenges, particularly related to the digital financial literacy of business actors. This study aims to analyze the influence of digital financial literacy on the interest in using digital payments among MSME actors in Jambesari Darussholah District, Bondowoso Regency. This study uses a quantitative approach with an explanatory survey method involving 80 respondents from MSME actors. Data were collected thru a structured Likert scale questionnaire and analyzed using simple linear regression analysis. The research results show that digital financial literacy has a positive and significant effect on the interest in using digital payments (t value = 9.172; sig. = 0.000), with a contribution of 51.9% (R² = 0.519). These findings imply the need for enhanced digital financial literacy education programs for MSME actors to encourage the accelerated adoption of digital payments in semi-rural areas.